Migration due to sexual orientation and gender identity - Nascimento, Daniel Braga; Haas, Emilie de; Baggio, Roberta Camineiro (Revista do Direito, 2017)
The concept of the term refugee is set out in Art. 1, item I of the Law 9.474 / 97 of the Foreign Statute of Brazil, which defines a refugee as any individual with a well-founded fear of persecution due to race, religion, nationality, political opinion or social group. The Convention of 1951 does not establish a specific category for persecution related to sexual orientation or gender identity. In many countries homosexuality is punished by imprisonment, or the death penalty (Saudi Arabia, Iran, Yemen, Mauritania and Sudan, as well as in regions of Nigeria and Somalia), among other penalties that deny full citizenship, segregate, discriminate and deny rights to this group. Due to the persecution these individuals suffer in their home countries, it is possible to ask: were gay, lesbian, bisexual, transgender and intersex individuals included in the social group category due to its flexible criteria? The United States, Canada and several European countries have been accepting refugee applications for individuals with well-founded fear of persecution because of their sexual orientation or gender identity. By employing this criterion, the CONARE (National Committee for Refugees of Brazil) has granted refuge to gay, lesbian, bisexual, transgender and intersex individuals who are persecuted in their home countries due to their sexual orientation or gender identity. This article explores the concept of the term refugee and its expansion over the past years, focusing especially on the basis of the refugee criterion related to social group. The aim is therefore to analyze the category of social group in the concept of refugee. It also aims to examine the possibility of framing said populations in the category of social group in order to facilitate their obtainment of a Refugee status.